2020
DOI: 10.3390/nu12123675
|View full text |Cite
|
Sign up to set email alerts
|

Low Oral Bioavailability and Partial Gut Microbiotic and Phase II Metabolism of Brussels/Witloof Chicory Sesquiterpene Lactones in Healthy Humans

Abstract: Free and glycosylated sesquiterpene lactones (SLs), which are abundant in leafy vegetables including Brussels/witloof chicory, possess health-promoting effects in vivo. However, the pharmacokinetics of dietary source of SLs remain largely unknown. In this open-label and single-dose trial, sixteen healthy volunteers consumed 150 g of Brussels/witloof chicory juice containing 48.77 μmol SLs in 5 min. Blood, urine, and fecal samples were collected before and after chicory consumption in 24 h. No SLs were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Chicory sesquiterpene lactones have been reported to possess considerable biological activities and have been used in traditional medicines for centuries. Moreover, foods rich in SLs might be considered to be part of a healthy, balanced diet [ 37 ]. There is a noticeable lack of scientific studies that analyzed the content of SLs in food products, as well as the influence of processing conditions on the content of these bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Chicory sesquiterpene lactones have been reported to possess considerable biological activities and have been used in traditional medicines for centuries. Moreover, foods rich in SLs might be considered to be part of a healthy, balanced diet [ 37 ]. There is a noticeable lack of scientific studies that analyzed the content of SLs in food products, as well as the influence of processing conditions on the content of these bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The serum concentration of free lactucin and 11(S),13-dihydrolactucin after consumption of a serving of chicory juice containing 49 µmol of total SLs showed a Cmax of 0.143 and 0.116 µmol/L, respectively, and the Cmax of total SLs amounted to 0.284 µmol/L determined by Weng et al [37]. It suggests the in vivo efficacy of the tested extracts containing even about 200 µmol of total SLs converted to lactucin in a dosage of 2 g of extracts with approx.…”
Section: Evaluation Of Sesquiterpene Lactones Preparations As Ache In...mentioning
confidence: 87%
“…The concentrations upon which SL molecules are pharmacologically active are not well defined, and although SLs are described as poorly bioavailable [ 28 ], the aforementioned in vivo reports show that, in many cases, orally administered SLs are pharmacologically active against inflammation. These conclusions highlight the anti-inflammatory potential of orally administered SLs, thereby reinforcing the importance of studying their pharmacokinetic (ADME—Absorption, Distribution, Metabolism, Excretion) profile of these molecules.…”
Section: Anti-inflammatory Potential Of Sesquiterpene Lactonesmentioning
confidence: 99%
“…In a study involving healthy volunteers, Weng et al [ 28 ] evaluated the absorption, metabolism, and excretion of SLs after the ingestion of a Brussels/witloof chicory juice. Although the largest percentage of consumed SLs (mainly lactucin and some derivatives) was recovered in the fecal samples (43.76%), 7.03% was detected in the blood samples and 1.13% in the urine samples, suggesting the systemic distribution of the compounds [ 28 ]. The authors also demonstrated that ingested SLs undergo phase II metabolism (glucuronidation and sulfation) and are metabolized by the gut microbiota in healthy humans [ 28 ].…”
Section: Pharmacokinetic Concernsmentioning
confidence: 99%
See 1 more Smart Citation